Conventional and audiovisual teaching materials to be used by the teacher to the english productive skills development. - Pinto Sánchez, Yazmín Lisseth (Machala : Universidad Técnica de Machala, 2015)
HABILIDADES convencionales y materiales didácticos audiovisuales son herramientas que un maestro es responsable de su selección para el desarrollo de una clase. Un material de enseñanza convencional es todo lo que se ha utilizado tradicionalmente, tales como portafolios, pizarra, periódicos, revistas, etc., que están disponibles para la mayoría de los profesores que quieren implementar algo diferente en el desarrollo de sus clases, mientras audiovisual requiere más esfuerzo para ponerlas en práctica en un aula, se trata de televisión, películas y vídeos, todos ellos seleccionados con el fin de ser implementadas en el sector educativo.
Conventional and audiovisual teaching materials are tools that a teacher is responsible of its selection for the development of a class. A conventional teaching material is everything that has been traditionally used, such as flip charts, whiteboard, newspapers, magazines and so on, which are available to most teachers who want to implement something different in the develop of their classes, while audiovisual require more effort to implement them in a classroom, these are television, films and videos, all these selected with the purpose to be implemented in the educational sector.
Keywords: MATERIAL; AUDIOVISUAL; TEACHING; SKILL